Effect of Lavender (Lavandula angustifolia) Essential Oil on Acute Inflammatory Response - Cardia, Gabriel Fernando Esteves (Evid Based Complement Alternat Med, 2018)
Lavandula angustifolia is a plant of Lamiaceae family, with many therapeutic properties and biological activities, such as anticonvulsant, anxiolytic, antioxidant, anti-inflammatory, and antimicrobial activities. The aim of this study was to evaluate the effect of Lavandula angustifolia Mill. essential oil (LEO) on acute inflammatory response. LEO was analyzed using gas chromatography-mass spectrometry (GC-MS) and nuclear magnetic resonance spectroscopy (NMR) methods and showed predominance of 1,8-cineole (39.83%), borneol (22.63%), and camphor (22.12%). LEO at concentrations of 0.5, 1, 3, and 10 μg/ml did not present in vitro cytotoxicity. Additionally, LEO did not stimulate the leukocyte chemotaxis in vitro. The LEO topical application at concentrations of 0.25, 0.5, and 1 mg/ear reduced edema formation, myeloperoxidase (MPO) activity, and nitric oxide (NO) production in croton oil-induced ear edema model. In carrageenan-induced paw edema model, LEO treatment at doses of 75, 100, and 250 mg/kg reduced edema formation, MPO activity, and NO production. In dextran-induced paw edema model, LEO at doses of 75 and 100 mg/kg reduced paw edema and MPO activity. In conclusion, LEO presented anti-inflammatory activity, and the mechanism proposed of LEO seems to be, at least in part, involving the participation of prostanoids, NO, proinflammatory cytokines, and histamine.